Tathwir Mâddah Qawa'id Al Nahw Bi Istikhdam Al Wasâit Articulate Storyline Fi al Madrasah al Mutawassitah Al Islāmiyyah - Haryati, Ratih; Hamid, Muhammad Abdul; Hasan, Nur (STIQ Amuntai, 2025)
This study addresses issues in teaching Nahwu grammar at Madrasah Tsanawiyah Kalipucang Pangandaran, such as low student motivation, limited interaction, inadequate teaching media, and challenges in comprehending complex materials. The research aims to develop, evaluate, and measure the effectiveness of teaching materials for Nahwu grammar in Articulate Storyline interactive multimedia. We employed the research and development (R&D) method with the ADDIE model (analysis, design, development, implementation, and evaluation). Data was collected through observations, interviews, questionnaires, and tests. Material and language experts, along with media experts, conducted feasibility tests, and 24 eighth-grade students participated in product trials. We administered pre-tests and post-tests to measure effectiveness. The findings indicate that the study successfully developed Nahwu grammar teaching materials for eighth-grade students using Articulate Storyline. The materials included identity menus, content (jumlah mufidah, ismiyah, fi’liyah), interactive quizzes, and developer menus. Validation results from experts showed feasibility scores of 81.33% and 96%, respectively, rated as